The Effectiveness Of The Al-Ta'bir Al-Mushawar Strategy In Improving Maharah Al-Kalam - Ibnu Rawandhy N. Hula; Nur Hanifa Basarata; Suharia Sarif (CV. Ulil Albab Corp, 2022)
Various kinds of efforts are made by educators for the implementation of good and effective learning. In improving speaking skills there are several strategies used, one of which is the al-ta'bir al-mushawwar strategy. The purpose of this study was to describe the effectiveness of the al-ta'bir al-mushawwar strategy in improving students' speaking skills. In addition, this study aims to determine the advantages and disadvantages of this strategy. The method used in this research is quantitative with One Group pretest-posttest design. In analyzing the data of this study, a different t-test was used with data collection techniques of observation, interviews, and tests. The sample used was class VIII B, which consisted of 10 students. It is said so because the data analyzed are the numbers obtained from the test results (pre-test and post-test) of students. The results of this study indicate that the al-ta'bir mushawwar strategy is effective in improving students' maharah al-kalam